Hubungan Asupan Protein dan Zat Besi dengan Kejadian Anemia pada Remaja Putri di SMPN 18 Banjarmasin - Fitrah Noor Pratama; Meitria Syahadatina Noor; Farida Heriyani (Homeostasis, 2020)
Abstract: Anemia is a condition of decreased hemoglobin levels in the blood. Data from the Banjarmasin City Health Department 2018 the incidence of anemia in adolescents was 924 cases, consisting 884 young women and 40 young men. One factor that may cause anemia is the lack of protein and iron intake. The purpose of this study was to determine and analyze the relationship of protein and iron intake with the incidence of anemia in adolescent girls at SMPN 18 Banjarmasin. The method used in this study is analytic observational with a cross-sectional approach. The population was the entire female students at SMPN 18 Banjarmasin with 88 females as the sample. The sampling technique used a proportional random sampling. Chi square test was used to help analyze this research. The results of this study were 47% of respondents with anemia and 53% without anemia, 60% of inadequate protein intake and 40% of adequate protein intake, 70% of inadequate iron intake and 30% of adequate iron intake. Chi-square test shows the results with a value of p = 0.149 for the association of protein intake of adolescents females with anemia and a value of p = 0.084 for the association of iron intake of adolescents females with anemia. In conclusion, there is no association between protein and iron intake with the occurrence of anemia in adolescents females at SMPN 18 Banjarmasin. Keywords : protein intake, iron intake, anemia, adolescents females. Abstrak: Anemia merupakan keadaan terjadinya penurunan kadar Hb darah di dalam tubuh. Data Dinas Kesehatan Kota Banjarmasin 2018 angka kejadian anemia pada remaja sebesar 924 kasus, 884 remaja putri dan 40 remaja putra. Asupan protein dan zat besi yang kurang merupakan salah satu faktor kejadian anemia. Metode observasional analitik digunakan pada penelitian ini dengan pendekatan cross sectional. Sampel penelitian adalah remaja putri SMPN 18 Banjarmasin dengan jumlah 88 orang. Pengambilan sampel dengan proportional random sampling.  Data hasil uji chi-square menunjukan responden yang mengalami anemia 47% dan tidak anemia 53%, asupan protein yang tidak terpenuhi sebanyak 60% dan yang terpenuhi sebanyak 40%, asupan zat besi yang tidak terpenuhi sebanyak 70% dan yang terpenuhi sebanyak 30%. Hasil analisis uji chi square menunjukkan nilai p=0,149 untuk hubungan asupan protein dengan anemia dan nilai p=0,084 untuk hubungan asupan zat besi dengan kejadian anemia. Hasil pada penelitian ini menunjukan tidak ada hubungan asupan protein dan zat besi dengan kejadian anemia pada remaja putri di SMP Negeri 18 Banjarmasin. Kata-kata kunci: asupan protein, asupan zat besi, anemia, remaja putri